Hydrological balance of two Mediterranean forested catchments (Prades, northeast Spain) - Piñol, J; LLEDO, M J; Escarre, A (Hydrological Sciences Journal, 1991)
Abstract Precipitation and discharge have been measured for several years in two small forested catchments located in the Mediterranean area of Spain. Actual evapotranspiration has been calculated as the difference between annual precipitation and discharge. Results show that: (a) most of the precipitation is evaporated rather than lost by streamflow, even in the most humid years; (b) there is a high inter-annual variability both in discharge and evapotranspiration; and (c) annual evapotranspiration correlates significantly with annual precipitation, in contrast to the constancy of annual evaporation in catchments of wet, colder climates. Finally, a simple expression is proposed in order to calculate annual actual evaporation from the ratio of precipitation to potential evapotranspiration. This expression uses a derived exponent, k, which takes into account the characteristics of individual catchments.
doi: 10.1080/02626669109492492
Keywords: Catchments; evapotranspiration (voyant); hydrological response; Precipitation